Reactive Oxygen Species Production in Peripheral Blood Neutrophils of Obstructive Sleep Apnea Patients. (12th May 2013) - Pilkauskaite, Guoda; Miliauskas, Skaidrius; Sakalauskas, Raimundas
Abstract : Obstructive sleep apnea (OSA) as well as obesity is associated with increased production of reactive oxygen species (ROS). Neutrophils produce great amounts of ROS. The aim was to evaluate peripheral blood neutrophils ROS production in men with OSA and to establish relations with disease severity and obesity. Methods . Forty-six men with OSA and 10 controls were investigated. OSA was confirmed by polysomnography (PSG), when apnea/hypopnea index was >5/h. Body mass index (BMI) was evaluated. Neutrophils were isolated from peripheral blood in the morning after PSG. Dihydrorhodamine-123 was used for ROS detection. Data is presented as median (25th and 75th percentiles). All subjects were divided into four groups: nonobese mild-to-moderate OSA, obese mild-to-moderate OSA, nonobese severe OSA, and obese severe OSA. Results . Neutrophil ROS production was higher in nonobese severe OSA group compared to nonobese mild-to-moderate OSA (mean fluorescence intensity (MFI) 213.4 (89.0–238.9) versus 44.5 (20.5–58.4), P < 0.05 ). In obese patient groups, ROS production was more increased in severe OSA compared to mild-to-moderate OSA group (MFI 74.5 (47.9–182.4) versus 31.0 (14.8–53.8), P < 0.05 ). It did not differ in the groups with different BMI and the same severity of OSA. Conclusion . Increased neutrophil ROS production was related to more severe OSA but not obesity.